The pot that Juan Built - Andrews-Goebel, Nancy (Lee & Low Books, 2002)
A cumulative rhyme summarizes the life's work of renowned Mexican potter, Juan Quezada. Additional information describes the process he uses to create his pots after the style of the Casas Grandes people.